An investigation of the role of C-terminal tensin-like (Cten) gene in colorectal cancer - Albasri, Abdulkader (2011)
The C-terminal tensin-like (Cten) gene is a member of the tensin family and is localised at the cytoplasmic tail of β-integrin. It is involved in various biological events although the role of in the development of colorectal cancer (CRC) is uncertain. In order to study this, the expression of Cten during the development of CRC was initially evaluated using immunohistochemistry (IHC) on colorectal adenomas and carcinomas. Positive immunoreactivity for Cten was observed in 317/342 (92.6%) of CRC and 19/20 (90%) of colorectal adenoma. High Cten expression was significantly associated with advance Dukes stage (p=0.001), lymph node metastasis (p<0.001), extra-mural vascular invasion (p=0.001) and distant metastases (p=0.008). Survival analysis demonstrated that patients with high Cten expression had significantly shorter disease free survival (DFS) on univariate analysis (p<0.001) a trend towards Cten expression as an independent predictor of DFS on multivariate analysis (p=0.071). To further test the association with metastasis, the role of Cten in metastasis was tested by (a) intrasplenic injection of CRC cells stably transfected with Green Fluorescent Protein (GFP) tagged Cten into nude mice and (b) testing a series of primary CRCs and their metastases by IHC. Compared with control mice (injected with cells transfected with GFP empty vector), mice injected with cells expressing Cten developed larger tumours in the spleen (p=0.03) and liver (p=0.05). Compared with primary tumours, the metastatic deposits had a significantly higher frequency of nuclear localisation of Cten (p=0.002). To further investigate the potential role of Cten in metastasis, in-vitro models were used to investigate Cten function. Ectopic expression of Cten in the HCT116 CRC cell line (which expresses low levels of Cten) caused changes in cell morphology and increased cell motility (both migration and invasion). Conversely, the reciprocal Cten knock-down experiments in SW620 CRC cell line (which expresses high levels of Cten) resulted in inhibition of both cell migration and invasion. Since Cten is in complex with integrins at focal adhesions, its interactiosn with integrin-linked kinase (ILK), focal adhesion kinase (FAK) and CD24 were tested. Cten was shown to regulate ILK, FAK and CD24. Moreover, inhibition of CD24 after forced expression of Cten abrogated the Cten-mediated effects on both cell motility and protein levels of ILK and FAK. The studies were expanded and Cten expression was tested by IHC in another cancer model i.e. breast cancer (BC).Consistent with the data from CRC, increased Cten expression in BC was found to be associated with poor prognostic variables and shorter disease free survival.